Intelligent Association Rules for Innovative SME Collaboration - SENNAROĞLU, BAHAR (SPRINGER-VERLAG BERLIN, 2015)
SMEs are encouraged to collaborate for research and innovation in order to survive in tough global competition. Even the technology SMEs with high knowledge capital have the fear to collaborate with other SMEs or bigger companies. This study aims to illuminate the preferences in customer, supplier and competitor collaboration within industry or inter industry. A survey is run on more than 110 companies and Machine Learning methods are used to define the association rules that will lead for success.
Keywords: Collaborative innovation; Association rules; SVM; SOM; RESEARCH-AND-DEVELOPMENT; KNOWLEDGE; PERFORMANCE; SECTOR